Estimation of the depth and volume of surface runoff of the main basins feeding into Sawa Lake using remote sensing and GIS techniques - Gareeb, Duaa M.; Yaseen, Ali M. (Al-Adab Journal, 2021)
This research deals with estimating the depth of runoff using the (SCS-CN) equation of the American Soil Conservation Services, as well as estimating the potential surface runoff volume of Lake Sawa, which is one of the important and common methods for calculating the volume of surface runoff. Estimating the volume of runoff of the basins that feed Sawa Lake is very important; to estimate the amount of water that can feed the lake through the surface runoff that subsequently enters the groundwater to feed the groundwater aquifers represented by the formations of the Euphrates, Dammam and Al-Ras. The equation was applied by making a classification of the land cover in the study area and this classification of the land units must be identical with the classification of the American Soil Conservation Service and the corresponding values (CN). Then he created a soil texture database that relied on the field survey of the study area, and took samples of soil for the purpose of analyzing its texture, on the basis of which a map of the hydrological groups of soil (A, B, C) was extracted, which reflects the nature of its texture and permeability, the amount of the volume of surface runoff, and the more The soil was soft-textured and less permeable, the greater the volume of runoff, represented in the study area by the hydrological group (C), while group (A) was considered to have high permeability, and represented a lack of surface runoff. The depth of the surface runoff in the case of dry soil was (0.22 mm), while in the normal case of soil moisture, the depth of the runoff was (0.68 mm). As for the volume of surface runoff in the dry case, it amounted to (0.83 million m3), and in the second case the normal surface runoff volume was (25.38 million m3).